Preoperative imaging predicts coracoid graft size and restoration of the glenoid track in Latarjet procedures - Stephanie A. Boden, MD; Brian M. Godshaw, MD; Jonathan D. Hughes, MD; Volker Musahl, MD; Albert Lin, MD; Bryson P. Lesniak, MD (JSES International)
Background: Glenoid bone grafting procedures are often utilized to address glenoid bone loss in patients with recurrent shoulder instability. The purpose of this study was to determine if preoperative advanced imaging can accurately predict coracoid graft size and conversion of off-track to on-track Hill-Sachs lesions in patients undergoing Latarjet procedures. Methods: Patients who underwent Latarjet procedure for shoulder instability at a single institution from 2012 to 2020 with preoperative and postoperative advanced shoulder imaging (computerized tomography or magnetic resonance imaging scans) were retrospectively reviewed. Glenoid diameter, Hill-Sachs interval (HSI), and measurements of the coracoid length, depth, and height were measured on preoperative imaging. Glenoid track (GT), percent glenoid bone loss, predicted restoration of GT, and the difference between HSI and GT (ΔHSI-GT) were calculated. Results: Seventeen patients with a mean age of 25 ± 9 years met inclusion criteria. Average glenoid bone loss preoperatively was 24 ± 7% and average HSI was 27 ± 5mm. The Latarjet procedure reconstructed 116 ± 8% of the native glenoid, and 104 ± 8% of the predicted diameter. Of the 15 patients that had off-track lesions preoperatively, 11 were successfully converted to on-track lesions (73%). The 4 persistent off-track lesions had a significantly higher HSI (32 ± 2 mm vs. 26 ± 4 mm, P = .002). Preoperative measurements accurately predicted postoperative GT status in 94% of cases. At a mean follow-up of 2 years, there was no significant difference in recurrence rate or rate of revision stabilization procedures between patients with on-track versus persistent off-track humeral lesions. Conclusion: Preoperative advanced imaging measurements can accurately predict whether an off-track Hill-Sachs can be converted to on-track after Latarjet procedure, further enhancing shoulder stability.